Market discounts and shareholder benefits: Evidence from Australian REIT private placements. Issue 6 (26th August 2014) - Ratcliffe, Christopher; Dimovski, Bill
Abstract : Purpose: – The purpose of this paper is to examine the impacts of private placement announcements by Australian Real Estate Investment Trusts (A-REITs) on existing shareholders. The study examines 96 A-REIT private placements from January 2000 to December 2012. Design/methodology/approach: – Utilising event study methodology the authors examine the impact on existing shareholders wealth by measuring the abnormal returns (AR) around the placement announcement. The authors extend the analysis to model the A-REITs ARs against a number of explanatory variables to investigate the possible drivers for the observed event study results. Findings: – The results support the information signalling hypothesis, in that existing investors in A-REITs earn negative and significant cumulative ARs of −1.3 per cent over the three-day event window [−1, +1]. This result is in contrast to prior studies conducted on industrial firms, for example; Hertzel and Smith (1993), Krishnamurthy et al. (2005) and Wruck and Wu (2009). Practical implications: – Regression analysis shows A-REITs trading at a premium to net tangible assets and A-REITs that use placement funds for their core business have a positive impact on announcement ARs. Originality/value: – This paper adds to the existing literature surrounding private placements and is the first paper, to the authors' knowledge, to examine the impact of Australian REITs.